Pengaruh Bauran Pemasaran Ritel terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan Pada Konsumen Alfamart di Kecamatan Tembalang Semarang - Arvinia Herawati; Ari Pradhanawati; Reni Shinta Dewi (Universitas Diponegoro, 2013)
The development of modern retailers is increased rapidly. The increae of existing modern retailer influenced by the increasing number of consumers who want to shop with easy and comfort. The purpose of this study is to determine the effect of the retail marketing mix on customer loyalty through customer satisfaction on consumer Alfamart in District Tembalang Semarang. Which in this study retail marketing mix is ​​divided into three variables, namely merchandising, basic principles and services. This type of research is explanatory. The sampling technique used purposive sampling a total of 100 people and measurement scale using Likert Scale. In the analysis of the data using simple linear regression, multiple regression with SPSS 16.0 and Path Analysis. Based on calculations indicate that the retail marketing mix variables simultaneously exerting influence on customer satisfaction in the amount of 62.7%. While customer satisfaction has a positive and significant effect on customer loyalty is equal to 46.4%. This means that the better the retail marketing mix will lead to high customer satisfaction and thereby increasing the level of customer loyalty.